Estimation of pulmonary artery pressure with transesophageal echocardiography: An observer-blinded test accuracy study. Issue 33 (20th August 2021) - Mora, Bruno; Roth, Dominik; Bernardi, Martin H.; Base, Eva; Weber, Ulrike
Abstract : Abstract: With the declining use of the pulmonary artery catheter (PAC), transesophageal echocardiography (TEE) has become an appealing alternative to obtain pulmonary artery pressure non-invasively using the simplified Bernoulli equation. The validation of this method in the perioperative setting has been scarce with no clear recommendations about which view is the most accurate to estimate right ventricular systolic pressure (RVSP). Therefore, we performed a prospective, observer-blinded, diagnostic test accuracy study to assess the difference in systolic pulmonary artery pressure (sysPAP) measuring both, invasively sysPAP and estimated RVSP with TEE in 3 different views: the mid-esophageal (ME) 4Chamber, the ME right ventricular (RV) inflow-outflow and the ME modified bicaval view. To show a clinically significant difference of at least 10% in RVSP, we included 40 cardiac surgical patients divided into 3 subgroups: Patients with mild to moderate tricuspid regurgitation (TR) and mean PAP <25 mm Hg, patients with mild to moderate TR and mean PAP≥ 25 mm Hg, and patients with severe TR. For the whole cohort, bias of estimated RVSP compared to measured sysPAP was 5.27 mm Hg, precision was 7.96 mm Hg, limits of agreement were −10.66 to 21.19 mm Hg. The best agreement between the 2 methods was found in patients with severe TR and in the ME RV inflow-outflow and the modified bicaval view. Good Doppler signals were available in 35% and 46% in these views, and in 20% in the ME 4 chamber view. The estimation of the sysPAP by TEE cannot be considered reliable in the clinical perioperative setting. Only measurements that provide a full Doppler envelope show sufficient precision to provide accurate estimations.